Impact of psychological stress and mammary tumour growth on structural and functional protein expression in cognitive brain areas - Alzboon, Walla' (2025)
Aims: Cognitive impairments are commonly reported across breast cancer patients and frequently attributed to the toxic side effects of chemotherapy treatment. However, it is evident that 35% of breast cancer patients experience cognitive impairments prior to chemotherapy. This suggests that tumour growth itself and/or the diagnosis-related stress might contribute to the development of cancer-related cognitive impairments (CRCI). The main aim of this thesis is to investigate the effect of tumour growth and diagnosis-related stress on the development of pre-treatment cognitive impairments.